Simulation of lamination orientation for carbon fiber reinforced polymer as a wrapping structure on piping system - M. Letchumanan, Shaktivell (2021)
Carbon Fiber Reinforced Polymer (CFRP) was designed, simulated and evaluated as a wrapping material on defected pipe using computational approach. This composite material was considered as a unique wrapping material as it may have the combined characteristics of the constituents or have substantially different properties than the individual constituents. Specifically, this research evaluates the capability of CFRP as a wrapper through SolidWorks Simulation using the static analysis and computational fluid dynamics (CFD) analysis. This approach gives a preliminary consideration and justification on choosing the optimized lamination orientation of CFRP in real cases based on the simulated data. Various orientations were simulated and analysed throughout this research. Based on all the simulation analysis, the CFRP wrapper with quasi -isotropic lamination with the 8 plies (45°/90°/0°/45°)